2018
DOI: 10.1088/1361-6498/aac698
|View full text |Cite
|
Sign up to set email alerts
|

Natural levels of polonium-210 in urine

Abstract: This paper presents a review and analysis of available data on background levels of polonium-210 in urine. It was established that 819 measurements could be considered to correspond to natural background levels, excluding a large number of values identified by the original investigators as potentially due to an artificial source or due to recognised enhancement of dietary intake. Almost 550 measurements were extracted from studies reported in the literature; additional measurements were contributions of previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Based on an early and rapid review of natural background levels of 210 Po in urine, a value of 30 mBq d -1 was chosen as an excretion rate above which intake was unlikely to be wholly attributable to natural dietary sources. The extensive analysis by Hodgson (2017) showed that while there was a very large range in individual values of from 0.3 to 170 mBq d -1 , more than 90% of the measurements were less than 30 mBq d -1 , supporting the early judgment. Separate analyses of data for individual countries showed that 95% or more of results were below 30 mBq d -1 in most cases, including the UK, but that China and Italy were notable exceptions for which more than 20% of values were above this level.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Based on an early and rapid review of natural background levels of 210 Po in urine, a value of 30 mBq d -1 was chosen as an excretion rate above which intake was unlikely to be wholly attributable to natural dietary sources. The extensive analysis by Hodgson (2017) showed that while there was a very large range in individual values of from 0.3 to 170 mBq d -1 , more than 90% of the measurements were less than 30 mBq d -1 , supporting the early judgment. Separate analyses of data for individual countries showed that 95% or more of results were below 30 mBq d -1 in most cases, including the UK, but that China and Italy were notable exceptions for which more than 20% of values were above this level.…”
Section: Discussionmentioning
confidence: 79%
“…Separate analysis of data for smokers and non-smokers suggested a modest increase in smokers of up to around 5 mBq d -1 . Reflecting the importance of dietary differences such as seafood consumption, a marked difference between countries was observed in the range of results (Hodgson 2017). While for most countries, 95% or more of results were below 30 mBq d -1 , China and Italy were notable exceptions, with greater than 20% of values above this level.…”
Section: Natural Background Levels Of 210 Po In Urinementioning
confidence: 99%
See 3 more Smart Citations